TRADEMARK NAMING ETHICS AND ITS IMPLICATIONS FOR HALAL STATUS ACCORDING TO ISLAMIC LAW - Riskia Ulfa; Fakhrurrazi M Yunus (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This study comprehensively explores the issue of poorly chosen names that contain negative connotations for culinary products and their impact on the halal status of food. The primary focus is on a food stall named "nasi bebek kuntilanak" (fried duck rice with the name kuntilanak, a ghost figure in Indonesian folklore). The approach used in this research is sociological-legal, involving the collection of primary information through interviews and direct observations, as well as the use of secondary data sourced from religious regulations, such as the fatwa issued by the Indonesian Ulema Council (MUI), and legislation. The main findings indicate that the business owner violated regulations by labeling their product "kuntilanak," which contradicts the legal stipulations outlined in the MUI Fatwa Number 44 of 2020 regarding the use of names, appearances, and packaging designs that cannot obtain halal certification. This regulation explicitly prohibits the labeling of halal on products that contain harmful elements such as disbelief, sinful actions, or connotations that do not align with Islamic values. The use of the term "kuntilanak," which is provocative and sensational, has the potential to influence public perception regarding the halal status of a food product. Although the composition of ingredients and food processing techniques meet halal requirements, the use of a name with negative implications becomes an obstacle in the halal certification process by the Halal Product Assurance Agency. This research is significant in understanding the cultural and social impacts of naming practices considered deviant. Therefore, this study emphasizes the importance of educating culinary business actors to use names that align with Sharia values, thereby strengthening consumer trust, maintaining a business reputation, and contributing to the enhancement of the national halal product ecosystem.